2015
DOI: 10.1108/imefm-09-2012-0087
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the ethical aspects of Islamic banking

Abstract: Purpose – The purpose of this paper is to look into the ethical practices of a profit-driven financial institution that is currently adopting Islamic banking and whether it can actually be ethical from an Islamic perspective. The recent decade has seen an upsurge of the increasingly integration of ethical management into operational strategies by businesses across the globe. Like any other religion, Islam wants its followers to be truthful and honest and to be compliant with its teachings and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 15 publications
1
41
0
1
Order By: Relevance
“…Islamic banking is labelled as competitors to the existing conventional banking instead of complementing and providing alternative products. The word Islamic is also the main impediment for customers, especially those of different religions and faith to approach Islamic banks compared to conventional banks (Gilani, 2015). Therefore, for all other Islamic banking products and services should consider rebranding the products without including the word Islamic, instead, highlight shariah compliance as the main attraction and attention-grabbing products for them to be visible locally and internationally.…”
Section: Islamic Credit Cards: the Badmentioning
confidence: 99%
See 2 more Smart Citations
“…Islamic banking is labelled as competitors to the existing conventional banking instead of complementing and providing alternative products. The word Islamic is also the main impediment for customers, especially those of different religions and faith to approach Islamic banks compared to conventional banks (Gilani, 2015). Therefore, for all other Islamic banking products and services should consider rebranding the products without including the word Islamic, instead, highlight shariah compliance as the main attraction and attention-grabbing products for them to be visible locally and internationally.…”
Section: Islamic Credit Cards: the Badmentioning
confidence: 99%
“…As Gilani (2015) stated, the word Islamic banking is a significant impediment for customers from other religions to work closely and for the banks to gain more market shares than conventional banking. He further added that the Islamic banking stands for a unique Islamic religious following and therefore, restraints its territory to Muslim customers only (Gilani, 2015). Another displeasing fact about Islamic financial services is the permanent barrier of the terminology Islamic in the product range offered to the market compared to the conventional products (Wilson, 2011).…”
Section: Shariah Compliant Credit Cardsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mudhārabah contract, the investment amount (deposit amount) might lessen due to the nonperformance of the financing activities. Bank gives no guarantee to depositors since its status of investment account (Anuar et al, 2014;Gilani, 2015).…”
Section: Literature Review the Irregular Deposit And The Reserve Bankmentioning
confidence: 99%
“…As Ahmed (2011) asserted that Islamic banks have challenges in applying ethical values in a highly rival market environment. Some studies revealed that there is a gap in ethics from Islamic point of view and the reality in today's Islamic banks' practices (Pesendorfer and Lehner, 2016;Mansour et.al., 2015;Al-Jarhi, 2010) whereas other studies suggested that some Islamic banks function based on ethical guidelines (Gilani, 2015;Slimene et.al., 2014). Though not conclusive, most of the studies illustrate that Islamic banks are deviating from some ethical practices and this situation needs due consideration from Shariah advisory committees and regulatory bodies.…”
mentioning
confidence: 99%